Influence of Salinity Levels on Seedling Parameters Of Different Tomato Genotypes - M Kumar; K Vanitha (Bangladesh Journal of Botany, 2023)
In the present study, 50 genotypes of tomatoes were tested in the roll towel method using seven levels of salt concentration from 0 to 120 mM of NaCl with an interval of 20 mM at laboratory conditions. Results showed that out of 50 genotypes, only 38 tomato genotypes germinated under a moderate salinity level of 80mM NaCl. The highest seedling fresh and dry weights were observed in LE-14 (0.271 and 0.045, respectively) under moderate salinity level which were on par with the genotypes LE-1, LE-1020, CLNR 2123, H24, IIVR88783 and LE-411. The highest fresh and dry seedling tolerance index were observed in IIVR-88783 (94.3 and 104.7) with an 80mM salinity level, which was on par with the genotypes, LE-1, LE- 1020, Arka Abhay, CLNR 2123, EC 164677, EC164838, EC164863, EC326146, IIVR 88783, IIVR EC 2494, IIVREC2798, LCR 2, LE-14, Pb-Rathak, Punjab Bagkoa and Punjab Bas with a moderate salinity level of 80 mM of NaCl. The genotypes LE-14, LE-1020, LE-1, LE-411, CLNR2123, H-24, IIVR-88783 and IIVR-EC2494 were found to be superior over 38 genotypes with the seedling characters. Bangladesh J. Bot. 52(2): 307-314, 2023 (June)